2006
DOI: 10.1007/s10238-006-0112-9
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of chromosome 21 aneuploidies in breast fibroadenomas by fluorescence in situ hybridisation

Abstract: Fibroadenoma (FA) is a benign breast tumour that occurs in about 25% of women. Cytogenetic studies suggest that numerical chromosomal aberrations may contribute to tumorigenesis, but chromosomal instability is still poorly characterised in breast cancer. The aim of this study was to investigate numerical alterations of chromosome 21 in 15 breast FAs. All samples were analysed by classical cytogenetics and by fluorescence in situ hybridisation (FISH) for chromosome 21 DNA sequences. Classical cytogenetics analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In this case, the GPs’ reasoning is based on what is medically possible. Medical expertise is an essential part of medical professionalism and moreover prized by the patient [20]. However, the danger lies in GPs equating medical professionalism with medical expertise, so that patient issues may be condensed to purely what is clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the GPs’ reasoning is based on what is medically possible. Medical expertise is an essential part of medical professionalism and moreover prized by the patient [20]. However, the danger lies in GPs equating medical professionalism with medical expertise, so that patient issues may be condensed to purely what is clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic theories showed that specific karyotypic variations of cancer cells were higher in comparison to conventional mutation Li et al 2005), and that different types of structural chromosome abnormalities (Johansson et al 1996) and abnormalities in the chromosome number of aneuplody type (Duesberg et al 2004;Soares et al 2006) are the basis of carcinogenesis.…”
mentioning
confidence: 99%
“…156 Multispectral FISH has also been used in pancreatic tissue, 102,331 to analyze a break-apart ALK probe for various phases of cell division in myofibroblastic tumors, 235 and to assess MED12 mutations in smooth muscle tumors and uterine fibroid and their relationship to cytogenetic subgroups. 194,195 MSI has been used to image chromosome 21 aneuploidies in breast fibroadenomas; 289 in NBS1 mutations, immunodeficiency, lymphoid malignancy, and early T-cell development; 269 in investigations of fusion genes (EWSR1-NFATC1) in hemangioma of the bone; 10 and in PPAR gamma-specific probes for the detection of PAX8/PPAR gamma translocation in follicular thyroid neoplasms 282 or thyroid carcinoma samples. 150…”
Section: Msi Of Ffpe Tissues: Technological Aspectsmentioning
confidence: 99%